The Influence of Video Game Training with and without Subpatelar Bandage in Mobility and Gait Speed on Elderly Female Fallers - Isabela Feitosa de Carvalho; Gianluca Loyolla Montanari Leme; Marcos Eduardo Scheicher (Journal of Aging Research)
Objectives. The aim of the study was to investigate the effect of balance training with Nintendo Wii technology, with and without the use of additional sensory information (subpatellar bandage), in the functional mobility and gait speed of elderly female fallers. Methods. Twenty elderly women were divided into two groups: group I: trained with the use of the Nintendo Wii; group II: trained using the Nintendo Wii and the addition of sensory information (subpatellar bandage). The functional mobility was assessed with the Timed up and Go test (TUG) and gait speed with the 10 m test. The tests were carried out with and without the use of the subpatellar bandage. The training was carried out within sessions of 30 minutes, twice a week, using three different games (Penguin Slide, Table Tilt, and Tightrope). Results. There was an increase in the gait speed and a decrease in the TUG time in both groups, independently of the sensory condition used (p<0.05). In the short term, the subpatellar bandage improved the TUG time (p<0.05) and the gait speed (p<0.01). Conclusion. The training for postural balance with virtual reality was effective for improving functional mobility and gait speed of elderly female fallers. The subpatellar bandage did not maximize the effect of training.